Interface Layers of Niobium Nitride Thin Films. (December 2019) - Lubenchenko, A V; Iachuk, V A; Krause, S; Pavolotsky, A B; Ivanov, D A; Lubenchenko, O I; Pavlov, O N
Abstract: Intermediate layers formed by thin NbN films are studied. A surface phase of NbN different from the bulk one under the oxide layer and a layer consisting of NbN x -SiO y between the film and the substrate are found.